Does Public Concern Affect the Greenhouse Gas Emissions of Oil and Gas Production, Through Logistics? - Vitharana, S.P.H Vitharana; Kandegama, W.M.W.Wishwajith (International Journal of Supply Chain Management, 2019)
Today’s globalized world is well aware that the fossil fuel industry is the main contributor to greenhouse gas (GHG) emissions that cause global warming and climate change. Negative public opinion about the oil and gas industry is rising globally. A growing number of global citizens are adept at shifting public sentiment about oil and gas industry emissions, particularly in Logistics industry. In this context, oil and gas companies have begun to substantially invest in renewable energy sources in a bid to diversify their oil and gas product portfolios to mitigate climate change risks in line with Logistics industry. This energy transition is influenced by rising social concern about climate change. Energy transition is an environmental management system and its outcomes benefit dry zone agriculture and many other business sectors. In this research work, we used qualitative data obtained from real social surveys conducted by Yale University and Pew Research Center from 2013 to 2019 and the emissions data disclosed by oil and gas companies for the same time period, and we use Excel spreadsheets to give graphic and numeric outputs in a time-series analysis. The outcome of the analysis tells us the relationship between the social concern about climate change and emissions reduction and the environmental performance of oil and gas companies. Our analysis shows that public concern about climate change is always high in Europe compared to the United States, but it has been increasing steadily on both continents, in Europe from 54% in 2015 to 79% in 2019 and in the United States from 40% in 2013 to 69% in 2019. Our graphical analysis reveals social concern has had a real impact on climate change, leading to a reduction of over ten million tons of emissions annually in 2013–2019 on both sides of the Atlantic, while meeting growing energy demand particularly in the United States.